161k views
0 votes
If f(x) = -4x+3 and g(x) = 3 +2x-4 find (f+g) (x)

User Pravy
by
5.3k points

2 Answers

3 votes

Answer:

Please be careful with your typing [f(x)=-sqrt(x)+6 ... right? g(x)=-4*sqrt(x)-3 ... or -4*sqrt(x)+3 ... one or the other, right?

If so, you are dilating by a factor of 4, -1 versus -4 as multiplier of sqrt(x); and, translating up 3 units (6 versus 3) or 9 units (6 versus -3).

Explanation:

User Kaycee
by
4.8k points
0 votes

Answer:

-2x+2

Explanation:

f(x) = -4x+3 and g(x) = 3 +2x-4

Note what you put for g(x) simplifies to 2x-1

(f+g) (x) = -4x+3+ 3 +2x-4

Combine like terms

= -2x+2

User Vu Phung
by
5.5k points